Monolophus unifolius (Zingiberaceae), a new species from Sagaing Region, northern Myanmar - Ding, Hong-Bo; Yang, Bin; Zeng, Xiao-Dong; Thwe, Phyo Phyo; Zuo, Yun-Juan; Tan, Yun-Hong (Phytotaxa, 2025)
A new species, namely Monolophus unifolius, from Northern Myanmar is described and illustrated. Its systematic placement was confirmed through molecular phylogenetic analyses using nuclear ribosomal ITS sequences. Morphologically, this new species is notably distinct from other Monolophus species in having only one leaf blade per leafy shoot and white labellum tinged with yellow spot at the throat. A key to the Monolophus species currently recorded in Myanmar is also provided.